â€œMatuya Mettaâ€ Creation of Javanese Dance Drama from the Story of Phra Lor - Oky Bima Reza Afrita (IJCAS (International Journal of Creative and Arts Studies), 2023)
Matuya Metta is a Javanese dance-drama performance in the Yogyakarta dance style in the form of group choreography. This drama features the story of Phra Lor, famous in Thai literature. Matuya comes from the word â€œmatuâ€, meaning mother, and â€œmettaâ€ meaning love. So, "Matuya Metta" means a mother's love. The reason for choosing the Phra Lor story is that there are similarities between the Thai a siang nam ritual and the Javanese tradition called tapa kungkum. Matuya Metta dance drama is expressed dramatically and symbolically. It is danced by three dancers and the piece contains in five segments. Javanese dance in the Yogyakarta style is the basis for the movements, namely the characters of alusan and putri luruh. The music is adapted to the atmosphere in the story and the characterâ€™s movements according to contemporary Javanese tradition. The performance combines recordings of gamelan instruments with digital music. The makeup and costume designs are inspired by Javanese dance and Thai ornaments. This dance-drama also uses minimal staging properties and settings to beautify the performance and help the audience understand the story.Â â€œMatuya Mettaâ€ Penciptaan Drama Tari Jawa dari Kisah Phra Lor Abstrak Matuya Metta adalah pertunjukan drama tari Jawa gaya Yogyakarta dalam bentuk koreografi kelompok. Drama ini menampilkan kisah Phra Lor yang terkenal dalam sastra Thailand. Matuya berasal dari kata â€œmatuâ€ yang berarti ibu, dan â€œmettaâ€ yang berarti cinta. Jadi, "Matuya Metta" berarti cinta seorang ibu. Alasan dipilihnya cerita Phra Lor adalah karena ada kesamaan antara ritual siang nam orang Thailand dengan tradisi Jawa yang disebut tapa kungkum. Drama tari Matuya Metta diekspresikan secara dramatis dan simbolis. Tarian ini ditarikan oleh tiga orang penari dan terdiri dari lima segmen. Tari Jawa gaya Yogyakarta menjadi dasar geraknya yaitu tokoh alusan dan putri luruh. Musiknya disesuaikan dengan suasana dalam cerita dan gerak-gerik tokoh sesuai tradisi Jawa kontemporer. Pertunjukan tersebut menggabungkan rekaman instrumen gamelan dengan musik digital. Desain tata rias dan kostumnya terinspirasi dari tarian Jawa dan ornamen Thailand. Drama tari ini juga menggunakan properti dan setting pementasan yang minim untuk mempercantik pertunjukan dan membantu penonton memahami ceritanya.